Технические развертки изделий из листового материала - Высоцкая Н. Н. Наталья Николаевна; Иерусалимский А. М. Александр Михайлович; Невельсон Р. А. Раиса Александровна; Федоренко В. А. Виктор Алексеевич (Ленинград, Машиностроение, 1968)
Исключено из фонда НТБ ТПУ